METHODS OF EDUCATION DEVELOPMENT MANAGEMENT IN THE FIELD OF PHYSICAL CULTURE AND SPORTS OF POLAND - Oleksandr Mozolev (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The author researches the content of management activities to develop education in the field of physical culture and sports in Poland. The analysis of revealing the term "method" by Polish scientists has been made. The concept of "management method" is defined as a way to implement administrative functions by organizing preliminary impact of management subject on object of management with the purpose of implementation of its public functions or a set of controls that are used in an appropriate manner that can most effectively achieve their managerial objectives defining the qualitative aspect of system administration. The concept "management methods for developing education in the field of physical culture and sports in Poland" is formulated. The content of management methods for developing education in the field of physical culture and sports in Poland in which the author includes: economic; social and political; administrative; ethical methods; methods of cognitive activity; forecasting; planning; management decision-making and control.